2009
DOI: 10.1016/j.chemosphere.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Gas/particle partitioning and global distribution of polycyclic aromatic hydrocarbons – A modelling approach

Abstract: a b s t r a c tThe global atmospheric distribution and long-range transport (LRT) potential of three polycyclic aromatic hydrocarbons (PAH) -anthracene, fluoranthene and benzo [a]pyrene -are studied. The model used is a global aerosol-chemistry-transport-model, which is based on an atmospheric general circulation model. The model includes an in-built dynamic aerosol model coupled to two-dimensional surface compartments. Several parameterisations of gas/particle partitioning and different assumptions of degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 40 publications
2
94
0
Order By: Relevance
“…On the contrary, choosing the lower surface area of 3.6 m 2 g −1 reduced the contribution of adsorption onto soot to ≤2%. The results showed that the contributions from salts were negligible − adsorption to (NH 4 ) 2 SO 4 and NH 4 Cl contributed to <0.1% of the K P ; however, the magnitude of adsorption was much higher for (NH 4 ) 2 SO 4 (a factor of 30 ± 2) than for NH 4 Cl. Overall, the results suggest that adsorption to matrices other than soot may be neglected for modeling PAH gas-particle partitioning.…”
Section: Environmental Science and Technologymentioning
confidence: 86%
See 1 more Smart Citation
“…On the contrary, choosing the lower surface area of 3.6 m 2 g −1 reduced the contribution of adsorption onto soot to ≤2%. The results showed that the contributions from salts were negligible − adsorption to (NH 4 ) 2 SO 4 and NH 4 Cl contributed to <0.1% of the K P ; however, the magnitude of adsorption was much higher for (NH 4 ) 2 SO 4 (a factor of 30 ± 2) than for NH 4 Cl. Overall, the results suggest that adsorption to matrices other than soot may be neglected for modeling PAH gas-particle partitioning.…”
Section: Environmental Science and Technologymentioning
confidence: 86%
“…53 The minimum and maximum of these surface areas were also applied in order to explore the sensitivity of the model predictions. We acknowledge that the phases considered in the present study may not be fully available for PAH partitioning due to internal mixing and kinetic limitations related to OM phase-state 54 (slow diffusion in semisolid and solid phases) and that under high relative humidity (NH 4 ) 2 SO 4 and NH 4 Cl may be present in dissolved aqueous phase and subject to liquid−liquid phase separation with OM. 55 Moreover, as PM composition varies significantly with particle size, SOC sorption behavior is expected to be particle-size dependent.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Being generally partitioned between the gaseous and particulate phases (e.g. Lammel et al, 2009), the 4-, 5-and 6-ring PAHs are predominantly particle-bound due to their high molecular weights and low volatilities. Despite their well documented toxic potential on humans and ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the real environment, PACs with more than 4 rings, including reactive BaP, PER, and DahA, are mainly associated with particulate matter (Su et al, 2006;Yamasaki et al, 1982) and hence suffer from O 3 degradation to a lesser extent as they are partially shielded from gaseous oxidants by black carbon, organic matter, and the accumulation of atmospheric reaction products on the surface. (Jariyasopit et al, 2014;Lammel et al, 2009;Zhou et al, 2012) Furthermore, it is Fig. 2.…”
Section: And Si2 Supportingmentioning
confidence: 99%